Synthesis and Application of Selenium Nanoparticles for the Modulation of Inflammatory Diseases - Xinwei Bai; Tianchang Zhou; Xiao Wu; Jin Chang; Xiaoli Wu (Nano Biomedicine and Engineering, 2025)
Inflammation is a fundamental response process to injury, which is coordinated by various inflammatory mediators, including reactive oxygen species, inflammatory immune cells and cytokines. Excessive inflammatory responses can drive the development of numerous diseases, making modulation of inflammatory responses a crucial strategy in the treatment of inflammatory diseases. Selenium (Se), an essential trace element for human health, plays a crucial role in alleviating severe inflammatory diseases by scavenging free radicals, achieving antioxidant effects and modulating the innate and adaptive immune systems in the inflammatory microenvironment. Among the different forms of Se element, Selenium nanoparticles (SeNPs) stand out for their low toxicity and high utilization rate, offering them unique advantages in the fields of medicine and materials science. In addition, functional modification of SeNPs enhances their biological activities in modulating the process of inflammatory diseases. In this review, the construction of various types of SeNPs are firstly discussed. Then, we review the diagnosing effects of modified SeNPs and highlight their biomedical applications in the treatment of inflammation. Finally, we summarize the limitations in the current research of SeNPs as well as the major challenges in clinical transformation, and anticipate the application prospects of new functionalized SeNPs in the treatment of inflammatory diseases.